THE RETEXTUALIZATION OF MULTIMODAL TEXTS: A BIBLIOMETRIC RESEARCH ABOUT ITS APPROACH ON ENGLISH CLASSES - Rangel de Almeida, Camila; Dutra Ferreira, Esther; Marieli Pereira Caetano, Joane; Medeiros de Souza, Carlos Henrique (LINKSCIENCEPLACE, 2026)
Based on the reading and research on retextualization of multimodal texts, it was sought to observe scientific works about retextualization of multimodal text aimed at English Language teaching, aiming to analyze the existing works, the way their contents are presented and the quantitative of researches around this theme. At the outset, it will be demonstrated the work through multimodal texts, its importance and, consequently, the benefit occasioned by them for the students. besides the texts of Ribeiro (2016), Cristóvão e Pontara (2017), Fettermann (2017), Coscarelli (2016) e Catto (2013) as a theoretical support for the bibliographic part, methodologically, it is also a bibliometric research, from the databases of the platforms SciELO, Capes Newspapers and Scholar Google, which made possible to analyze the current database.